Correlation of Resting Elbow Angle with Spasticity in Chronic Stroke Survivors - Bhadane, Minal Y.; Gao, Fan; Francisco, Gerard E.; Zhou, Ping; Li, Sheng (Frontiers in Neurology, 2015)
Objective: To evaluate whether resting joint angle is indicative of severity of spasticity of the elbow flexors in chronic stroke survivors. Methods: Seventeen hemiparetic stroke subjects (male: n=13; female: n=4; age: 37-89 years; 11 right and 6 left hemiplegia; averaged 54.8 months after stroke, ranging 12-107 months) participated in the study. The number of subjects with modified Ashworth scale score (MAS) = 0, 1, 1+, 2, 3 was 3, 3, 5, 3, 3, respectively. In a single experimental session, resting elbow joint angle, MAS, and Tardieu scale score (Tardieu R1) were measured. A customized motorized stretching device was used to stretch elbow flexors at 5°/s, 50°/s, and 100°/s, respectively. Biomechanical responses (peak reflex torque and reflex stiffness) of elbow flexors were quantified. Correlation analyses between clinical and biomechanical assessments were performed. Results: Resting elbow joint angle showed a strong positive correlation with Tardieu R1 (r = 0.77, p<0.01) and a very strong negative correlation with MAS (r = −0.89, p<0.01). The resting angle also had strong correlations with biomechanical measures (r= −0.63 to −0.76, p<0.01). Conclusion: Our study provides experimental evidence for anecdotal observation that the resting elbow joint angle correlates with severity of spasticity in chronic stroke. Resting angle observation for spasticity assessment can and will be an easy, yet a valid way of spasticity estimation in clinical settings, particularly for small muscles or muscles which are not easily measurable by common clinical methods.